Short communication. Cloningand sequencing of partial genomic DNA fragments corresponding to the S11 and S12 alleles of the Spanish almond cultivar "Marcona" - Kodad, O.=700 1 Sanchez, A.; Saibo, N.; Alonso, J.M.; Oliveira, M.M.; Socias i Company, R.
(Es, En)
ilus., 14 ref.
Keywords: PRUNUS AMYGDALUS; PCR; CLONACION MOLECULAR; RIBONUCLEASAS; ESPAÑA